Morita-Baylis-Hillman reaction of masked 5-alkylidene-2-cyclopentenones: General entry to 5-alkylidene-2-(hydroxyalkyl)-2-cyclopentenones - Manat Pohmakotr (2018)
(Chemical Equation Presented) The reaction of masked 5-alkylidene-2- cyclopentenones with aldehydes catalyzed by tributylphosphine in the presence of phenol provided the corresponding Morita-Baylis-Hillman adducts, which were subjected to flash vacuum pyrolysis to afford 5-alkylidene-2-(hydroxyalkyl)-2- cyclopentenones. © 2007 American Chemical Society.